THE LANGUAGE SITUATION IN GREAT BRITAIN AND THE USA: LINGUISTIC SIGNIFICANCE AND NATURE OF TEXTS ON PUBLIC SIGNS THROUGH SEMIOTICS AND DISCOURSE ANALYSIS - Abduzoirova Nigora Abduxamid qizi (International Journal of Literature and Language Studies, 2026)
This study examines the linguistic landscapes of Great Britain and the United States, focusing on public signs and multilingualism. Using a comparative qualitative analysis, the research investigates how urban signage reflects language policy and immigrant communities. Findings reveal that while English dominates, multilingual signs in ethnic enclaves signal cultural identity and economic diversity. The study concludes that public signs function as symbolic markers of social inclusion. These results highlight the evolving nature of Western urban spaces as multilingual hubs, reflecting global migration trends.